Comparative Analysis of Moringa oleifera Lam. Leaves Ethanolic Extracts: Effects of Extraction Methods on Phytochemicals, Antioxidant, Antimicrobial, and In Ovo Profile - Sergio Liga; Ioana Zinuca Magyari-Pavel; Ștefana Avram; Daliana Ionela Minda; Ana-Maria Vlase; Delia Muntean; Laurian Vlase; Elena-Alina Moacă; Corina Danciu (Plants)
A comparative evaluation of Moringa oleifera Lam. ethanolic leaf extracts was performed using different extraction methods (maceration or ultrasound-assisted) and the qualitative and quantitative profile of the bioactive compounds contained were further assessed. The antioxidant potential and antimicrobial activity were evaluated, as well as the antiangiogenic effects through in ovo studies. Six ethanolic extracts were tested in this study. Moringa MAC 70% and Moringa US 70% extracts displayed the highest concentration of phenolic compounds and also showed a significant AOA at the highest tested dose. Regarding the antimicrobial effect, the extracts obtained with 70% ethanol (maceration or ultrasound-assisted) had antimicrobial activity against S. aureus, S. pyogenes and E. coli, followed by Candida parapsilosis. On the Pseudomonas aeruginosa strain, the extracts showed no effect. The HET-CAM assay showed that the extracts did not cause any irritation compared to the used positive control. Furthermore, the extracts Moringa MAC 70% and Moringa US 70% did not affect the normal process of blood vessel formation. The data obtained highlights that, from the six tested extracts, the ones obtained with 70% ethanol using maceration and ultrasound-assisted methods (Moringa MAC 70% and Moringa US 70%) showed the highest phenolic content and exhibited the strongest antioxidant activity. The same two extracts did not show signs of irritation in the HET-CAM model.